The great Gilly Hopkins [videorecording (DVD)] - Nélisse, Sophie; Bates, Kathy, 1948-; Stiles, Julia, 1981-; Paterson, Katherine (Lionsgate Premiere, 2016)
Gilly Hopkins has seen more than her share of foster homes and has outwitted every family she has lived with. In an effort to escape her new foster mother Maime Trotter's endless loving care, Gilly concocts a plan that she believes will bring her mother running to her rescue. But when the ploy blows up in Gilly's face it threatens to ruin the only chance she's ever had to be part of a real family.